Application Of Neuron Anatomy As A Source Of Inspiration Batik Design - Arif Pristianto; Nafi’ Ika Salsabella (International Forum of Researchers and Lecturers, 2023)
Batik is one of the creations of the Indonesian nation which has an aesthetic value that needs to be preserved and developed. The neuron batik design visualizes the beautiful and complex shapes and structures of neurons combined with floral motifs. Batik design inspiration can be found through anything. In creating this neuron batik design, inspiration was obtained during the learning process. In the science of physiotherapy, neurons are important structures that are studied and interrelated. The research was carried out using the method of literature study and exploration. The manufacturing process begins with making an initial sketch using a sketchbook and drawing pen which is done manually then developed and transferred to digital media with Corel Draw. The final stage of making this design is giving the base color and pattern color to be used. The motive elements contained in this Neuron batik have meaning and value in life, which is hoped that later people will be able to remember and practice through this batik.